Social iniquities in Primary Healthcare and intersectoral action: a descriptive study - Larissa Barros de Souza; Ricardo Alexandre Arcêncio; Fernanda Carla de Assis Cândido; Laura Terenciani Campoy; Denisse Andrea Cartagena-Ramos; Regina Célia Fiorati (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To analyze Primary Healthcare with regards to dealing with social inequities through actions targeted at Social Determinants of Health, from the perspective of Family Health Strategy Professionals. Methods: Descriptive study with a qualitative approach. Data were collected through focus groups and analyzed using Habermas's communicative action theory. Results: There were few intersectoral and assistance organization actions with clinical emphasis; municipal management for intersectoral actions shows a lack of planning and faces challenges; and there is little communication and articulation between the sectors. Final considerations: There are many challenges to be overcome by Primary Health Care to contemplate intersectoral actions targeted at Social Health Determinants, a demand inherent to the possibilities of advancing in the reduction of social and health-related inequalities.